2014
DOI: 10.7717/peerj.443
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MHCII variants associated with chlamydial disease in the koala (Phascolarctos cinereus)

Abstract: Chlamydiosis, the most common infectious disease in koalas, can cause chronic urogenital tract fibrosis and infertility. High titres of serum immunoglobulin G against 10 kDa and 60 kDa chlamydial heat-shock proteins (c-hsp10 and c-hsp60) are associated with fibrous occlusion of the koala uterus and uterine tube. Murine and human studies have identified associations between specific major histocompatibility complex class II (MHCII) alleles or genotypes, and higher c-hsp 60 antibody levels or chlamydia-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The 57 koalas with the most ocular microbiome reads maintained a comparable representation of chlamydia disease states and KoRV-B results to the overall population and were deemed suitable as a subset for MHC examination. Using the DNA extracted from whole blood, PCR for the DAb (271 bp product) and DBb (282 bp product) gene was carried out as previously described 21 , 41 . PCR products were cloned into pGEM-T-Easy TA cloning vector system (Promega) as per manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The 57 koalas with the most ocular microbiome reads maintained a comparable representation of chlamydia disease states and KoRV-B results to the overall population and were deemed suitable as a subset for MHC examination. Using the DNA extracted from whole blood, PCR for the DAb (271 bp product) and DBb (282 bp product) gene was carried out as previously described 21 , 41 . PCR products were cloned into pGEM-T-Easy TA cloning vector system (Promega) as per manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Finer detailed evolutionary analysis such as multilocus sequence typing (Jelocnik et al, 2013), which has been used to investigate the pathogenesis of C. pecorum infections in sheep (Jelocnik et al, 2014), or newly developed full-genome sequencing techniques (Bachmann et al, 2015) could be employed to further examine the relationship between C. pecorum strain type and the observed clinical signs. An analysis of host genetic factors, such as major histocompatibility complex class II variation (Lau et al, 2014), would also be useful for understanding the host-pathogen interaction. The publication of the koala genome will accelerate efforts in this area (Johnson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Further, overall, disease progression in SE Qld koalas was significantly associated with the Class II allele DBb 04. Interestingly, a study in NSW koalas reported significantly higher chlamydial-hsp60 antibody titres in koalas with DBb allele 04, suggesting this variant recognises and binds to c-hsp60 epitopes 17 . High c-hsp60 antibody titres in koalas have been associated with fibrous occlusion of the uterus or uterine tube, however their role in chlamydial pathogenesis in koalas remains unclear as they were also associated with lower levels of active inflammation and fewer chlamydial inclusions 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a complex range of factors is known to influence chlamydial disease progression in koalas, the koala's immune response to C. pecorum plays a key role and the MHC loci are known to be important in this response 17 . Our analysis of MHC alleles and urogenital tract disease progression in SE Qld populations identified two putative susceptibility (DCb 03, DBb 04) and protective variants (DAb 10, UC 01:01).…”
Section: Discussionmentioning
confidence: 99%